Faktor-Faktor Yang Mempengaruhi Produksi Usaha Tani Kopi Di Desa Waikanabu Kecamatan Tabundung Kabupaten Sumba Timur: Coffee, Influence, Waikanabu Village, Production - Jangga, Febianti Karanja; Mbana, Febyningsi Rambu Ladu (Sandalwood Journal Of Agribusiness And Agrotechnology, 2025)
The study was conducted with the aim of analyzing the average amount of coffee production in Waikanabu Village, Tabundung District, East Sumba Regency, and analyzing the factors that influence production. This study was conducted in Waikanabu Village, Tabundung District, East Sumba Regency, from July to August 2025. The population of this study was all farmers who carry out coffee farming in Waikanabu Village, Tabundung District, East Sumba Regency, totaling 120 farmers. Determination of the number of samples in this study was carried out using the Slovin formula, and the results of the calculation determined that the number of samples in this study was 55 coffee farmers in Waikanabu Village. Data analysis was carried out by tabulating data to determine the average amount of production, and multiple linear regression analysis to analyze the influence of production factors of land area, labor, costs, plant age, farmer experience, and selling price on coffee production in Waikanabu Village, Tabundung District, East Sumba Regency. The results of the study explain that the average amount of coffee production in Waikanabu Village is 157.73 Kg/Year. Partially, land area has a significant influence, while labor factors, production costs, plant age, farmer experience, and selling price do not have a significant influence on the amount of production in coffee farming in Waikanabu Village, Tabundung District, East Sumba Regency. Simultaneously, land area, labor, production costs, plant age, farmer experience, and selling price factors together have a significant influence on the amount of production in coffee farming in Waikanabu Village, Tabundung District, East Sumba Regency.